Evaluating Oculomotor Tests before and after Vestibular Rehabilitation in Patients with Parkinson’s Disease: A Pilot Pre-Post Study - Amirabas Abasi; Reza Hoseinabadi; Parvin Raji; Joseph H. Friedman; Mohammad-Reza Hadian (Parkinson's Disease)
Introduction. The elderly population is commonly affected by balance and gait disorders that increase the risk of falls. Pivotal systems for efficient postural control are sensory, motor, visual, vestibular, and cognitive. Disruption in any of these systems could lead to postural instability. Vestibular rehabilitation is a set of exercises that positively affect the primary components of the central sensory-motor integration, including somatosensory, visual, and vestibular systems. Accordingly, we hypothesized that vestibular rehabilitation exercises might improve both oculomotor functions and upright postural control in patients with Parkinson’s disease. Materials and Methods. 11 idiopathic Parkinson’s patients voluntarily participated in this study based on inclusion criteria: central vestibular dysfunction and the Hoehn and Yahr scale scores less than or equal to 3. Videonystagmography (VNG) and the Berg Balance Scale (BBS) scores were measured at the baseline. Then, the patients underwent vestibular rehabilitation training for 24 sessions (3 sessions per week). The VNG and BBS were measured again after 48 hours of the completion of the last session of the training. Result. After completing vestibular rehabilitation sessions, there were significant improvements in balance P≤0.001. Eye-tracking and gaze function statistically improved in 7 patients and 6 patients, respectively. Conclusion. Vestibular rehabilitation produced positive effects on oculomotor function and balance in a small cohort of people with PD. Consequently, it could be considered as a possible effective intervention for Parkinson’s patients. This trial is registered with IRCT201709123551N6.